FALSE ANEURYSM OF THE LEFT VENTRICLE: CASE REPORT WITH PRE- AND POSTOPERATIVE EVALUATION - Treistman, Bernardo (1978)
A 66-year-old woman developed chronic congestive heart failure after myocardial infarction of the anterior wall of the left ventricle. Angiographic studies revealed total proximal occlusion of the left anterior descending coronary artery and a large saccular aneurysm located on the anteroapical aspect of the left ventricle. Resection of a false aneurysm at operation resulted in improved cardiac function, and the patient made an uneventful recovery. Repeat evaluation six months later confirmed normal cardiac hemodynamics and left ventricular angiographic characteristics. To our knowledge, this is the first documented case of normalized heart function resulting from resection of a false aneurysm of the left ventricle. Functional classification according to the New York Heart Association improved dramatically, rising from Class IV preoperatively to Class I after operation.